Response priming in a go/nogo task: do we have to explain the go/nogo N2 effect in terms of response activation instead of inhibition? - Bruin, K.J; Wijers, A.A; van Staveren, A.S.J (Clinical neurophysiology, 2001)
Objectives: In the present study, we examined the effects of response priming on the event-related potentials (ERPs) evoked by target stimuli in a go/nogo task. Methods: In each trial, subjects were presented a cue and a target stimulus. The cue informed subjects about the following target in that trial, and therefore, also about the kind of response (right-hand response, left-hand response, no overt response) potentially to be given in that trial. Results: The traditional N2 and P3 go/nogo effects were replicated: the ERPs to nogo targets were negative compared to the ERPs evoked by go targets in the N2 latency range at frontal electrode sites, and the nogo P3s were more anteriorly distributed than the go P3s. Comparing the ERPs evoked by nogo targets, we found the P3, but not the N2, to be modulated by response priming. Conclusions: These results seem to indicate that the P3, but not the N2, is associated with response inhibition, or with an evaluation/decision process with regard to the expected and/or given response. It could be speculated that the traditional go/nogo N2 effect has to be explained in terms of response activation instead of response inhibition.